Bidirectional Relationship Between Osteoarthritis and Periodontitis: A Population-Based Cohort Study Over a 15-year Follow-Up - Ma, Kevin Sheng-Kai; Lai, Jung-Nien; Thota, Eshwar; Yip, Hei-Tung; Chin, Ning-Chien; Wei, James Cheng-Chung; Van Dyke, Thomas E. (Frontiers in Immunology, 2022)
Objective: To identify the relationship between osteoarthritis and periodontitis. Methods: 144,788 periodontitis patients and 144,788 propensity score-matched controls without history of periodontitis were enrolled in this cohort study. A Cox proportional hazard model was used to estimate the risk of osteoarthritis. Survival analysis was utilized to assess the time-dependent effect of periodontitis on osteoarthritis. Age and gender were stratified to identify subgroups at risk. A symmetrical case-control analysis was designed to determine the relationship between present periodontitis and history of osteoarthritis. Results: Patients with periodontitis had higher risk of osteoarthritis (Hazard ratio (HR) =1.15, 95% CI =1.12–1.17, P < 0.001) and severe osteoarthritis that led to total knee replacement or total hip replacement (TKR/THR) (HR =1.12, 95% CI =1.03–1.21, P < 0.01) than controls, which was time-dependent (log-rank test P < 0.01). The effect of periodontitis on osteoarthritis was significant in both genders and age subgroups over 30 years-old (all P < 0.001). Among them, females (HR=1.27, 95% CI = 1.13–1.42, P < 0.001) and patients aged over 51 (HR= 1.21, 95% CI =1.10-1.33, P < 0.001) with periodontitis were predisposed to severe osteoarthritis. In addition, periodontitis patients were more likely to have a history of osteoarthritis (OR = 1.11, 95% CI = 1.06 - 1.17, P < 0.001). Conclusions: These findings suggest an association between periodontitis and a higher risk of osteoarthritis, including severe osteoarthritis that led to TKR/THR. Likewise, periodontitis is more likely to develop following osteoarthritis. A bidirectional relationship between osteoarthritis and periodontitis was observed.